2014
DOI: 10.1002/stc.1655
|View full text |Cite
|
Sign up to set email alerts
|

Crack detection and characterization techniques-An overview

Abstract: SUMMARY Crack occurrence and propagation are among critical factors that affect the performance and lifespan of civil infrastructures such as bridges, pipelines, and so on. As a consequence, numerous crack detection and characterization techniques have been researched and developed in the past decades in the areas of SHM and non‐destructive evaluation (NDE). The significant amount of performed studies and the large number of publications give rise to the need to systematize, condensate, and summarize this enor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
123
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(138 citation statements)
references
References 78 publications
(111 reference statements)
0
123
0
Order By: Relevance
“…However, processing a large volume of images can be time consuming, and the robustness of results can be sensitive to the feature of specific types of cracks. A comprehensive review of crack detection methods can be found in Yao et al [7] Direct strain measurement has the potential to be very effective for crack detection since crack opening leads to abrupt strain change in the localized area. For this reason, both traditional metal foil gages [8] and fiber optic sensors [9] have been evaluated for crack detection.…”
Section: Introductionmentioning
confidence: 99%
“…However, processing a large volume of images can be time consuming, and the robustness of results can be sensitive to the feature of specific types of cracks. A comprehensive review of crack detection methods can be found in Yao et al [7] Direct strain measurement has the potential to be very effective for crack detection since crack opening leads to abrupt strain change in the localized area. For this reason, both traditional metal foil gages [8] and fiber optic sensors [9] have been evaluated for crack detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefrom, { } and {V } obtained by (1) are the real displacements of the structure. Similarly, the spline basis function ( ) can be constructed.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…where [ ] 1 and [ ] 1 are the concrete elastoplastic matrix and the concrete plastic matrix in the biaxial compressive stress state, respectively; and [ ] is the elastic matrix of concrete, which is expressed by…”
Section: The Elastoplastic Increment Constitutive Model Of Concretementioning
confidence: 99%
See 1 more Smart Citation
“…However, dense arrays of sensors are needed, which require high hardware installation and data management. On the other hand, the main advantage of indirect damage detection is its lower cost for hardware and installation and the challenge of this detection method is the reliability and accuracy [2,3]. In recent years, the increasing demand of control and monitoring of structures in industry has caused an evolution on how system maintenance is realized and as a consequence, the aforementioned challenges are being overcome, while SHM approaches are gaining interest [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%